Implementation of the 2013 Curriculum at the Elementary School Level - Tamara Bishofa'il Aisy; Imaya Syifaul Khayati; Alvina Marissa Zesa S (Prosiding University Research Colloquium, 2021)
Implementation of the 2013 curriculum is a challenge for the world of education.The 2013 curriculum is very different from the previous curriculum. The approach takenin learning the 2013 curriculum is to use a scientific approach where students are thecenter of learning. There are three assessment aspects of the 2013 curriculum, namelycognitive aspects (knowledge, psychomotor and attitudes. This research is a qualitativedescriptive study. Primary data sources were obtained from observations and interviewswith elementary school teachers. The results of the study were analyzed and explainedusing words. The results showed that some elementary schools have implemented the2013 curriculum in school learning. Although there are obstacles in its application, theschools are trying their best to achieve the goals of the 2013 curriculum. The 2013curriculum uses integrative thematic learning methods, scientific approaches, and alsoauthentic assessment.